ANALISIS KEPUTUSAN PEMBELIAN PADA RITEL MODERN - Muhamad Ridwan (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
The purpose of this study was to study the effect of services on purchasing decisions at Alfamart Serua Indah Branch, South Tangerang. The research design used in this study is causal quantitative associative with descriptive explanations. The analytical method used is multiple linear regression analysis with a sample of 97 and the sampling technique used is the Accidental Sampling technique. Hypothesis test results indicate that service quality has a positive and significant effect on purchasing decisions with a regression coefficient of 0.699 and a coefficient of determination of 48.3%. This means that service quality can explain purchasing decisions by 48.3%, while the remaining 51.7% is explained by other variables outside this study, for example location, price, promotion, image etc